Variation of Interleukin-8 (IL-8) Receptor Gene Based on Single Strand Conformation Polymorphism (SSCP) in Indonesian Friesian Holstein Dairy Cattle - Winaya, A; Rahayu, ID (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
Interleukin-8 (IL-8) receptor gene is response to bacterial invasion, endothelial and epithelial cells by release the chemokine interleukin-8 (IL-8). IL-8 mediates neutrophil function, allowing neutrophils to resolve bacterial infections by migrating through blood vessel walls and to the site of infection. IL-8 also impacts neutrophil killing and survival ability during the inflammatory response. Genes that associated with neutrophil function also has potency as a genetic marker for mastitis disease, the migration of neutrophil from blood to infections side is essentially to detect the mastitis pathogen in general. It has been known that mastitis disease was the major problem in dairy cattle industry since influencing the milk quality, especially in bacterial content. The aim of this research is to detect the variation of IL-8 receptor gene in Indonesian Frisien Holstein (FH) dairy cattle which keep by farmer at Pujon District of Malang Regency. DNA genom was extracted from whole blood cells by standart phenol-chloroform methods. PCR reaction was done by using genomic DNA as a template while primer was the set of nucleotide that flanking IL-8 receptor gene. Polymorphism analysis of IL-8 receptor gene was based on number and frequency of SSCP (Single Strand Conformation Polymorphism) pattern of PCR products. From research result showed that was found five patterns of SCCP from IL-8 receptor gene of Indonesian FH which came from Pujon District, Malang Regency. This is also illustrated that of IL-8 receptor gene of Indonesian FH dairy cattle was enough polymorphism. The number pattern of SSCP-1 and SSCP-2 were found higher than others. Also, those patterns less than 50 % of samples were suspected as sub clinical mastitis. It means that this preliminary study showed that SSCP-1 and SSCP-2 patterns could be as a candidate marker for mastitis resistance of Indonesian FH dairy cattle. While others patterns could be used in determination of IL-8 receptor gene polymorphism of Indonesian FH dairy cattle based on SCCP patterns. This is important because we need this data for completing the genetic variation of Indonesian cattle data base. (Animal Production 12(2): 118-123 (2010)Key Words : IL-8 gene, mastitis, SSCP, chemokine, Friesian Holstein